Purposeful Play: The Reception of Daniel 5–6 in Ludus Danielis - Votral, Rebekah Rochte (Journal of the bible and its reception, 2025)
Ludus Danielis is a famous piece of medieval drama that was composed in the late twelfth century by the clerics and students connected to the Beauvais Cathedral in northern France and committed to writing in the early thirteenth century. The musical drama retells the story of Daniel in the courts of Balthasar and Darius, including his experience in the lion’s den (Dan 5–6). The long-standing Christian tradition of interpreting Daniel as a prophet and even prefigurement of Christ finds new expression in the form and content of Ludus Danielis. The play has enjoyed immense scholarly attention focusing on its distinctive features, performance history, devotional impact, context amid other performance traditions, and most notably, its role as a corrective to the Feast of Fools tradition. A reexamination of how Ludus Danielis presents and interprets the biblical narrative suggests that the play served an additional purpose, responding to the theological and ecclesiological trends that shaped the period in which the play was composed, performed, and recorded. The persona of Daniel was an ideal candidate for establishing an imaginative space to help the young clerics engage those trends. The playful engagement between the source material and dramatic mechanisms established a symbolic space wherein the court tales of Daniel 5–6 became the language for negotiating the desired norms of clerical authority and personal piety. The formational playscape created by the ludic (game-like) nature of the plays empowered the young clerics to negotiate the evolving role of the subdeacon as well as the tensions between private devotion and increased ecclesial mediation, especially in the sacrament of the Eucharist. Through purposeful playfulness, Ludus Danielis utilized the person and story of Daniel to engage in instructional commentary and contemplative pilgrimage, encouraging ideal clerical identity and piety while also reinforcing the expanding mediatory role of the clergy.